Practical considerations for the field application of miniaturized portable Raman instrumentation for the identification of minerals - Vítek, Petr; Jehlička, Jan; Edwards, Howell G M (Applied spectroscopy, 2013)
The nondestructive identification of both inorganic and organic compounds without the need for chemical or mechanical sample preparation is an advantage of the Raman spectroscopic analytical technique when applied in situ using miniaturized equipment for the geosciences. This is critically assessed here for several real life geoscientific scenarios in which several groups of minerals were analyzed with emphasis on evaporites, carbonates, and selected types of dark minerals and weak Raman scatterers. The role of individual analytical instrumental parameters such as focal plane precision, exposure time, and ambient light conditions that can affect the acquisition and interpretation of spectroscopic data from these specimens in field conditions was also evaluated.
Keywords: miniaturizace; Spectrum Analysis, Raman; Ramanova spektroskopie; Equipment Design; minerály; design vybavení; Miniaturization; geologie; Equipment Failure Analysis; Minerals; Geology; analýza selhání vybavení